Energy recovery strategies for batteries providing frequency containment reserve in the Nordic power system. (December 2022) - Engelhardt, Jan; Thingvad, Andreas; Zepter, Jan Martin; Gabderakhmanova, Tatiana; Marinelli, Mattia
Abstract: Batteries are key components of future power systems with high shares of renewables. Their fast response enables them to contribute to one of the most crucial ancillary services — frequency containment reserve. However, longer periods with biased frequency pose challenges for batteries due to their limited energy capacity. This is particularly crucial in the Nordic synchronous area where 100 % certainty of delivery is required. The present study uses a simulation model with three years of historical frequency, market, and tariff data, to compare three energy management strategies that comply with the Nordic regulatory framework. The first two strategies both utilize an hourly adjustment of the reference power to, on average, recover the energy level to a desired value. In the first strategy, this energy is traded on the intraday market, while in the second strategy it is settled via the balancing market. The third strategy is based on an exemption agreement with the Danish transmission system operator. Since capacity payment is the strongest factor that determines the profit, the study derives maximum regulating power and annual profit as a function of the energy/power capacity ratio and the efficiency of the storage system. The highest regulating power and profit can be achieved when applying the exemption agreement. Where this agreement is not available, the battery operator should apply the second strategy and settle the energy costs through the balancing market. Trading the energy on the intraday market slightly reduces the energy costs, but allows for significantly lower regulating power and revenues.